ESTABLISHING REQUIREMENT IN TEACHING NEW AND RENEWABLE ENERGY - Meredita Susanty; Ariana Yunita; Erwin Setiawan (Universitas Muria Kudus, 2019)
The distinctive shortage in the availability of skilled labor in new and renewable energy sector becomes the issue that has been prevented this country in achieving the national energy mix in 2015 and 2050. Although both formal and non-formal education initiatives already exist to foster new and renewable energy education, the number of graduates cannot outpace the number of required labor. The number of graduates and their competencies must be considered because local labors are facing intense competition with foreign labors due to ASEAN Economic Community policy. This research aims to find a solution to address the educational issue in new and renewable energy education. This research is using iterative methodology from the software engineering domain to identify issues and problems in new and renewable energy education in Indonesia and suggested alternatives to address it. Combination of techniques (questionnaire, interview, studying documentation, and research a similar product) is used in requirement elicitation stage in order to provide multiple perspectives.